Model Pembelajaran Berbasis Kearifan Lokal Untuk Membangun Kognisi Sosial Dan Sikap Sosial Siswa SMP - Sugiantoro; Yuni Suprapto; Ali Imron (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
Education in the 21st century necessitates the cultivation of capabilities that integrate cognitive abilities, social skills, and character development. In the context of accelerating globalisation, local wisdom values are progressively marginalised, despite their crucial influence on the formation of students' identity, social empathy, and tolerance. This project seeks to create and evaluate the efficacy of a Social Studies (IPS) learning model grounded in local knowledge, referred to as the Social Cognition Construction Model Based on Local knowledge. The study utilised a Research and Development (R&D) methodology, adhering to the phases of the Borg & Gall development model, which include needs analysis, model design, expert validation, limited trials, and extensive implementation. Data were gathered by observation, questionnaires, and tests, then analysed employing both descriptive quantitative and qualitative methodologies. The findings demonstrate that the Social Cognition Construction Model Based on Local Wisdom is both valid and practicable, as per evaluations from experts and practitioners. Both the limited and extended trials evidenced the model’s efficacy in improving five critical dimensions of learning: cognitive abilities (from 54.64 to 77.16), learning observation / observation of student engagement (from 89.25 to 96.00), learning motivation (from 79.06 to 94.12), social attitudes (from 64.64 to 92.02), and nurturant effect (from 81.20 to 92.65). In conclusion, the Social Cognition Construction Model Based on Local Wisdom significantly enhances Social Studies learning outcomes and promotes the development of student character that values local traditions, cultivates social empathy, and encourages harmonious social interactions.